2019
DOI: 10.1111/cgf.13615
|View full text |Cite
|
Sign up to set email alerts
|

Local Editing of Procedural Models

Abstract: Procedural modeling is used across many industries for rapid 3D content creation. However, professional procedural tools often lack artistic control, requiring manual edits on baked results, diminishing the advantages of a procedural modeling pipeline. Previous approaches to enable local artistic control require special annotations of the procedural system and manual exploration of potential edit locations. Therefore, we propose a novel approach to discover meaningful and non‐redundant good edit locations (GEL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…many approaches on inverse procedural modeling target program generation from input specifications [TLL*11; VGA*12; GJB*20], but do not allow direct editing. While there is some work on local editing from program analysis [JPCS18; LSL*19], none of these methods allow users to control geometric edits directly while maintaining a working program. In concurrent work to ours, Gaillard et al [GKG*22] enable direct editing at the granularity of objects, and directly tackle exploring ambiguous edits made possible in part by a fast objective function.…”
Section: Background and Related Workmentioning
confidence: 99%
“…many approaches on inverse procedural modeling target program generation from input specifications [TLL*11; VGA*12; GJB*20], but do not allow direct editing. While there is some work on local editing from program analysis [JPCS18; LSL*19], none of these methods allow users to control geometric edits directly while maintaining a working program. In concurrent work to ours, Gaillard et al [GKG*22] enable direct editing at the granularity of objects, and directly tackle exploring ambiguous edits made possible in part by a fast objective function.…”
Section: Background and Related Workmentioning
confidence: 99%
“…While these methods allow for some control of the procedural generation, the edits are still indirect. In contrast, Lipp et al [LSL ∗ 19] showed a method that can automatically generate handles for “good edit locations”, enabling direct local editing of architectural, procedural models. Our method is similar in that it allows direct local edits.…”
Section: Related Workmentioning
confidence: 99%
“…[Barroso et al 2013] proposes to rewrite the rule set of a shape grammar (which may also be represented as a DAG as shown by [Patow 2012]). [Lipp et al 2019] transforms edits applied by the user on a particular instance of a generator into edits of the program that generates a procedural shape. [Lienhard et al 2017] proposes automatic grammar rewriting, thus synthesizing programs that are the interpolation of other input programs.…”
Section: Related Workmentioning
confidence: 99%